2016
DOI: 10.3389/fpsyg.2016.00803
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Unique Risk Factors Underlying Mathematical Disability and Reading and Spelling Disability

Abstract: High comorbidity rates have been reported between mathematical learning disabilities (MD) and reading and spelling disabilities (RSD). Research has identified skills related to math, such as number sense (NS) and visuospatial working memory (visuospatial WM), as well as to literacy, such as phonological awareness (PA), rapid automatized naming (RAN) and verbal short-term memory (Verbal STM). In order to explain the high comorbidity rates between MD and RSD, 7–11-year-old children were assessed on a range of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 65 publications
(104 reference statements)
3
63
3
2
Order By: Relevance
“…In addition, the connection between phonological abilities and retrieval of arithmetic facts can be based on a shared brain mechanism, the left angular gyrus (Dehaene et al, 2003). Our results suggest that impaired phonological awareness can partially explain the comorbidity between MD and RD, and in fact Slot, van Viersen, De Bree, and Kroesbergen (2016) found that impaired phonological awareness was a shared risk factor for pure MD, pure RD and partially explained the comorbidity between MD and RD.…”
Section: Comprehensionmentioning
confidence: 48%
See 1 more Smart Citation
“…In addition, the connection between phonological abilities and retrieval of arithmetic facts can be based on a shared brain mechanism, the left angular gyrus (Dehaene et al, 2003). Our results suggest that impaired phonological awareness can partially explain the comorbidity between MD and RD, and in fact Slot, van Viersen, De Bree, and Kroesbergen (2016) found that impaired phonological awareness was a shared risk factor for pure MD, pure RD and partially explained the comorbidity between MD and RD.…”
Section: Comprehensionmentioning
confidence: 48%
“…Wilson et al (2015) examined RAN performance among RD and MD adults and found similar deficits in both groups. Two recent studies found RAN deficits in children with both MD and RD (Donker, Kroesbergen, Slot, Van Viersen, & De Bree, 2016;Slot et al, 2016). Moreover, other studies found that RAN deficit was a shared risk factor between ADHD and reading (McGrath et al, 2011;Shanahan et al, 2006).…”
Section: The Role Of Perception Speed In Mathematics Abilitiesmentioning
confidence: 99%
“…Kroesbergen & Van Dijk, 2015;Toll et al, 2016). Of course, there are other domain general factors that influence mathematics, such as processing speed (e.g., Peterson et al, 2017;Willcutt et al, 2013), phonological skills (e.g., Barnes et al, 2014;Slot, Van Viersen, De Bree, & Kroesbergen, 2016), or other executive functions as inhibition and shifting (Friso- Van den Bos et al, 2013;. It is not yet clear how these variables are related to creativity, and further research could take these into account to get a more comprehensive understanding of the underlying factors of mathematics.…”
Section: Discussionmentioning
confidence: 99%
“…Working memory is a domain-general predictor, not only in mathematical development but also in other academic areas. Although several other cognitive factors have been related to math, such as processing speed (e.g., Peterson et al, 2017;Willcutt et al, 2013), or phonological skills (e.g., Barnes et al, 2014;Slot, Van Viersen, De Bree, & Kroesbergen, 2016), working memory and number sense together explain a substantial part of the variance in mathematics (e.g., 48-50% in Kroesbergen & Van Dijk, 2015; 24-28% in Toll, Kroesbergen, & Van Luit, 2016). These two factors are not only related to mathematics in typically developing (TD) children, but they have also repeatedly been found to explain differences between children with mathematical learning disabilities (MLD) and TD children (e.g., Geary, Hoard, Byrd-Craven, Nugent, & Numtee, 2007;Mazzocco, Feigenson, & Halberda, 2011;Mussolin, Mejias, & Noël, 2010;Piazza et al, 2010; Raghubar, jnc.psychopen.eu | 2363-8761 Barnes, & Hecht, 2010Schuchardt, Maehler, & Hasselhorn, 2008).…”
mentioning
confidence: 99%
“…Evidence shows that reading and mathematical abilities are correlated, and in particular that reading and mathematical disabilities often show comorbidity (Miles et al, 2001; Fuchs et al, 2004; Dirks et al, 2008; Rubinsten, 2008; Slot et al, 2016). Moreover, children with comorbid mathematics and reading disabilities tend to do less well on mathematical tasks than children with mathematical disabilities without reading disabilities (Jordan and Montani, 1997; Jordan and Hanich, 2000; Jordan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%